Adenoid cystic carcinoma of the head and neck: a retrospective multicenter study. (2nd January 2018) - Takebayashi, Shinji; Shinohara, Shogo; Tamaki, Hisanobu; Tateya, Ichiro; Kitamura, Morimasa; Mizuta, Masanobu; Tanaka, Shinzo; Kojima, Tsuyoshi; Asato, Ryo; Maetani, Toshiki; Ushiro, Koji; Kitani, Yoshiharu; et al.
Abstract: Background: Adenoid cystic carcinoma of the head and neck (ACCHN) is rare and difficult to study effective treatment at one institute. Our aim is to identify prognostic factors for this disease by conducting a multicenter study at 11 institutions in Japan. Methods: A retrospective multicenter study of ACCHN was performed. One hundred and three patients were identified between 2006 and 2015. The overall survival (OS) rate for all patients was calculated, and OS, locoregional control (LRC) rate, or no distant metastasis (NDM) rate was calculated for patients in that the surgery was performed without distant metastasis (DM). Statistical analyses were performed. Results: A significant difference with multivariate analysis was observed in patients in sublingual glands, stage IV and the use of radiation therapy ≥60Gy (sufficient RT) in OS for all patients. A significant difference was observed in the use of sufficient postoperative RT in the OS and the LRC rate, and in pathological surgical margins in the NDM rate. Conclusion: Sublingual glands or stage IV was a poorer, and sufficient RT was a better prognostic factor for ACCHN. Sufficient RT was effective to prevent local recurrence after surgical resection. Positive surgical margins caused an increase in DM.